Motion in Games 4th International Conference, MIG 2011, Edinburgh, UK, November 13-15, 2011. Proceedings - Allbeck, Jan M.; Faloutsos, Petros (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the 4th International Workshop on Motion in Games, held in Edinburgh, UK, in November 2011. The 30 revised full papers presented together with 8 revised poster papers in this volume were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on character animation, motion synthesis, physically-based character motion, behavior animation, animation systems, crowd simulation, as well as path planning and navigation.